2020
DOI: 10.1016/j.scitotenv.2020.137662
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on a new pomelo peel derived biochar for tetracycline antibiotics removal in swine wastewater

Abstract: Removal of tetracycline antibiotics (TCs) by biochar adsorption is emerging as a costeffective and environmentally friendly strategy. This study developed a novel pomelo peel derived biochar, which was prepared at 400 °C (BC-400) and 600 °C (BC-600) under nitrogen conditions. To enhance the adsorption capacity, BC-400 was further activated by KOH at 600 °C with a KOH: BC-400 ratio of 4:1. The activated biochar (BC-KOH) displayed a much larger surface area (2457.37 m 2 /g) and total pore volume (1.14 cm 3 /g) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(58 citation statements)
references
References 65 publications
(36 reference statements)
2
53
1
2
Order By: Relevance
“…On comparing R 2 , the pseudo-second-order kinetic model ( R 2 > 0.99) was found to be more apt for describing TCs adsorption on Fe(III)@CNFs than the pseudo-first-order kinetic model ( R 2 : 0.960, 0.964 and 0.968). Thus, the pseudo-second-order kinetic model represents the adsorption process of TCs on Fe(III)@CNFs, which is consistent with the findings of many TCs studies [ 59 , 60 , 62 , 72 , 73 ]. The adsorption of TCs on Fe(III)@CNFs is controlled with a chemical process, and the adsorption rate is proportional to the number of surface active sites [ 72 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…On comparing R 2 , the pseudo-second-order kinetic model ( R 2 > 0.99) was found to be more apt for describing TCs adsorption on Fe(III)@CNFs than the pseudo-first-order kinetic model ( R 2 : 0.960, 0.964 and 0.968). Thus, the pseudo-second-order kinetic model represents the adsorption process of TCs on Fe(III)@CNFs, which is consistent with the findings of many TCs studies [ 59 , 60 , 62 , 72 , 73 ]. The adsorption of TCs on Fe(III)@CNFs is controlled with a chemical process, and the adsorption rate is proportional to the number of surface active sites [ 72 ].…”
Section: Resultssupporting
confidence: 87%
“…Further details are presented in §3.7. Although initial pH has an impact on TCs adsorption by Fe(III)@CNFs, Fe(III)@CNFs provide better TCs adsorption performance in a wide pH range than other adsorbents [ 59 , 62 , 63 ]. In a typical WWTP, the pH of influent is usually 5.5–8.0 [ 64 ]; thus, Fe(III)@CNFs have the potential to remove TCs from actual wastewater and save the cost of reagents required for adjusting pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After three weeks of operation with the presence of SMs in the reactor, a pomelo peel derived biochar (0.5 g/L), which was activated by KOH, was added into the reactor. The production, activation and characteristics of a newly developed pomelo peel derived biochar have been described previously (Cheng et al, 2020c). In short, the surface area and total pore volume of this activated biochar is up to 2457.37 m 2 /g and 1.14 cm 3 /g.…”
Section: Experimental Setup and Operationmentioning
confidence: 99%
“…Previous reports found that pomelo peel is an attractive adsorbent precursor for adsorbing heavy metals [29], antibiotics [30,31], and organic pollutants [32,33]. In the interest of sustainability, this study selected pomelo peels to prepared AC (PPAC) for removing AR88.…”
Section: Introductionmentioning
confidence: 99%